2003
DOI: 10.1071/as02059
|View full text |Cite
|
Sign up to set email alerts
|

The Polarised Bent Jet of 3C 43

Abstract: Radio observations of linear polarisation provide a useful probe of the physical conditions in the gaseous environments of compact steep spectrum (CSS) sources. Here, we present polarimetric VLBA observations at 8.4 GHz of the CSS quasar 3C 43. The jet in this source curves gently up to about 220 mas from the core, at which point it bends sharply, probably due to a jet-cloud encounter. Regions of polarised emission are detected along the jet, while the core component shows no significant polarisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…VLBI observations were reported by Nan et al (1991), Spencer et al (1991), andFanti et al (2002). Polarimetric VLBI observations were performed by Mantovani et al (2003) at 8.4 GHz. These , 2, 4, 8, 16, 32, 64,128, 256, 512, 1024 mJy/beam.…”
Section: Comments On Individual Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…VLBI observations were reported by Nan et al (1991), Spencer et al (1991), andFanti et al (2002). Polarimetric VLBI observations were performed by Mantovani et al (2003) at 8.4 GHz. These , 2, 4, 8, 16, 32, 64,128, 256, 512, 1024 mJy/beam.…”
Section: Comments On Individual Sourcesmentioning
confidence: 99%
“…VLBI observations were reported by Nan et al (1991), Spencer et al (1991), and Fanti et al (2002). Polarimetric VLBI observations were performed by Mantovani et al (2003) at 8.4 GHz. These authors detected polarised emission along the jet with polarisation percentages up to 12%.…”
Section: +233 (3c 43) -mentioning
confidence: 99%
“…Results for the first two CSS quasars observed in our ongoing program, B0548 + 165 and B1524 − 136, are available in Mantovani et al (2002), while those for 3C 43 (B0127 + 233) are to be found in Mantovani et al (2003). The results for 3C 147 (B0538 + 498) were presented by Rossetti et al (2009).…”
Section: Introductionmentioning
confidence: 99%